Profile of health care workers in a context of instability: a cross-sectional study of four rural health zones in eastern DR Congo (lessons learned) - Charles Ruhangaza Mushagalusa; Daniel Garhalangwanamuntu Mayeri; Bertin Kasongo; Aimé Cikomola; Sammuel Lwamushi Makali; Amani Ngaboyeka; Lili Chishagala; Albert Mwembo; Abdon Mukalay; Ghislain Balaluka Bisimwa (BMC, 2023)
Abstract Background The crisis in human resources for health is observed worldwide, particularly in sub-Saharan Africa. Many studies have demonstrated the importance of human resources for health as a major pillar for the proper functioning of the health system, especially in fragile and conflict-affected contexts such as DR Congo. However, the aspects relating to human resources profile in relation to the level of performance of the health districts in a particular context of conflicts and multiform crises have not yet been described. Objective This study aims to describe the profile of staff working in rural health districts in a context of crisis and conflicts. Methods A cross-sectional study was carried out from May 15, 2017 to May 30, 2019 on 1090 health care workers (HCW) exhaustively chosen from four health districts in Eastern Democratic Republic of Congo (Idjwi, Katana, Mulungu and Walungu). Data were collected using a survey questionnaire. The Chi2 test was used for comparison of proportions and the Kruskal-Wallis test for medians. As measures of association, we calculated the odds ratios (OR) along with their 95% confidence interval. The α-error cut-off was set at 5%. Results In all the health districts the number of medical doctors was very insufficient with an average of 0.35 medical doctors per 10,000 inhabitants. However, the number of nurses was sufficient, with an average of 3 nurses per 5000 inhabitants; the nursing / medical staff (47%) were less represented than the administrative staff (53%). The median (Min-Max) age of all HCW was 46 (20-84) years and 32% of them were female. This was the same for the registration of staff in the civil service (obtaining a registration number). The mechanism of remuneration and payment of benefits, although a national responsibility, also suffered more in unstable districts. Twenty-one percent of the HCW had a monthly income of 151USD and above in the stable district; 9.2% in the intermediate and 0.9% in the unstable districts. Ninety-six percent of HCW do not receive Government' salary and 64% of them do not receive the Government bonus. Conclusion The context of instability compromises the performance of the health system by depriving it of competent personnel. This is the consequence of the weakening of the mechanisms for implementing the practices and policies related to its management. DR Congo authorities should develop incentive mechanisms to motivate young and trained HCW to work in unstable and intermediate health districts by improving their living and working conditions.